2011
DOI: 10.15376/biores.6.4.4886-4894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure duration on physical, mechanical, and combustibility characteristics of laminated veneer lumber (LVL) made with hybrid poplar clones

Abstract: Experimental eight-ply laminated veneer lumbers (LVLs) from rotary peeled I-214 (Populus x Euramericana) and I-77/51 (Populus deltoides)fast growing hybrid poplar clones were successfully manufactured using three different press durations (18, 24, and 30 min) with a melamine urea formaldehyde (MUF) adhesive. The effect of press durations on LVLs’ selected physical, mechanical, and combustibility characteristics were determined. The results showed that press duration affected dimensional stability (thickness sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The temperature applied during the production of the test specimens with PF may have caused to thermo-mechanical densification and consequently this situation may have been caused an increase in MOR and MOE. In previous studies, it was reported that the mechanical properties of bonded wood materials produced using different adhesives change depended on the type of adhesive, press pressure, press temperature, and press time (Uysal et al 2010;Altinok et al 2011;Kurt et al 2011;Onat and Özdemir 2020).…”
Section: Experimental Groups Heat Treatment Temperaturesmentioning
confidence: 99%
“…The temperature applied during the production of the test specimens with PF may have caused to thermo-mechanical densification and consequently this situation may have been caused an increase in MOR and MOE. In previous studies, it was reported that the mechanical properties of bonded wood materials produced using different adhesives change depended on the type of adhesive, press pressure, press temperature, and press time (Uysal et al 2010;Altinok et al 2011;Kurt et al 2011;Onat and Özdemir 2020).…”
Section: Experimental Groups Heat Treatment Temperaturesmentioning
confidence: 99%
“…The problem with boron compounds is their inherent low solubility into wood as highlighted by (Nunes et al, 2023). Factors such as the wood type, sample size, preservative concentration, and preservative treatment type often vary from studies as they contribute significantly to the efficacy of the treatment such as in Colakoglu et al (2003), Kurt (2008), Yusof et al (2023).…”
Section: Introductionmentioning
confidence: 99%
“…Gluing, pressing, and curing are key steps in LVLs manufacturing that determine strength and durability (Kurt et al 2011). The quality and success of the pressing operation depends on suitable heat, press duration, and press pressure.…”
Section: Introductionmentioning
confidence: 99%